2021
DOI: 10.1177/00368504211026119
|View full text |Cite
|
Sign up to set email alerts
|

Circulating furin, IL-6, and presepsin levels and disease severity in SARS-CoV-2–infected patients

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in a vast number of infections and deaths that deeply affect the world. When the virus encounters the host cell, it binds to angiotensin-converting enzyme 2, then the S protein of the virus is broken down by the transmembrane protease serine 2 with the help of furin, allowing the virus to enter the cell. The elevated inflammatory cytokines suggest that a cytokine sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Kocyigit, et al . [ 24 ] reported that presepsin and IL-6 levels significantly increased according to COVID-19 disease severity and positively correlated with each other and COVID-19 disease severity. Zaninotto, et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kocyigit, et al . [ 24 ] reported that presepsin and IL-6 levels significantly increased according to COVID-19 disease severity and positively correlated with each other and COVID-19 disease severity. Zaninotto, et al .…”
Section: Discussionmentioning
confidence: 99%
“…Increased PCT levels may be associated with disease severity and mortality in COVID-19 patients [ 11 - 13 , 17 - 20 ]. Presepsin, a 13-kDa glycoprotein cleavage N-terminal fragment of CD14, is released into circulation by pro-inflammatory signals during infection and has diagnostic and prognostic values in sepsis [ 21 - 24 ]. In COVID-19, presepsin was suggested as a predictive biomarker for disease severity [ 24 - 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that PSS is a useful biomarker for assessing the severity and predicting mortality in patients with COVID-19. In a study by Kocyigit et al [27], PSS levels were significantly increased in the severe group compared with the mild and moderate groups of patients with COVID-19. In accordance with our findings, previous studies found that the PSS levels were significantly elevated in nonsurvivors than in survivors [16,28].…”
Section: Discussionmentioning
confidence: 89%
“…77 Nevertheless, high circulating levels of furin have been reported in COVID-19 patients, a critical factor that determines disease severity and cardiovascular adverse events. 79 Furthermore, elevated levels of furin were also reported in peripheral blood of HF patients. 80 Hence, furin inhibition might reduce viral load and cardiovascular damage in COVID-19 patients.…”
Section: Epigenetic Regulation Of Biomolecules That Affect Sars-cov-2...mentioning
confidence: 98%